К изучению кормовых связей тлей рода Pemphigus Нагtig (Homoptera, Aphidoidea) - Дорошина, Л.П. (Вестник зоологии, 1975)
With the aim of finding secondary hosts of Pemphigus populi Courch., P. lich- tensteini Tullgr and P. vesicarius and thus determining taxonomic differentiation of these Pemphigus from P. fuscicornis Koch., a common circle of food relations of Pemphigus from the Kerch Peninsula was studied by the method of soil excavations and examination of herbaceous plants. It is determined that the common circle of food relations includes 40 species of herbaceous plants. This considerably increases guarantees for experimental determination of the secondary hosts of the above-mentioned Pemphigus.